KEABSAHAN WEWENANG KEPALA KANTOR PERTANAHAN MENERBITKAN SERTIPIKAT HAK MILIK KEMUDIAN DIUBAH MENJADI SERTIPIKAT HAK GUNA BANGUNAN - Pondaag, Fenny (JURNAL MEDIA HUKUM DAN PERADILAN, 2019)
The subject matter of the study of the Authorization of the Authorities of the Head of the Land Office issues a certificate of ownership of the Land and then changes it to the Certificate of HGB, with the formulation of the problem of the Authorization of the Authority of the Head of the Land Office issuing the Certificate of Ownership and then it is changed to the Certificate of the HGB and the legal protection of the land holder over the actions of the Head of the Land Office . The following conclusions are obtained: The validity of the Head of the Land Office of Gowa Regency issues several certificates of ownership, explained that, the Head of the Land Office has the authority to issue certificates of land rights, but in issuing such certificates are not based on AUPB, including the principle of legal certainty, the principle of expediency, the principle of impartiality, the principle of good service. The Head of the Land Office of Gowa Regency should not issue it, because procedurally and legislation is not fulfilled, so that the certificate of ownership that is issued becomes invalid. Legal protection of land holders from the actions of the Head of the Land Office issuing certificates on behalf of the developer, preventively by submitting an objection to the issuance of the certificates to the Land Office. Objections are filed in writing to the certificate holder and the Head of the Land Office concerned or do not file a lawsuit to the Court regarding the control of the land or the issuance of the certificate, on the basis of the issuance of the certificate does not meet the requirements of the laws and regulations, especially the accuracy requirements. The reality of the objection that was submitted did not get a response from the Head of the Goa District Land Office, so the next step using the basis of repressive legal protection sued the Head of the Goa District Land Office, on the basis of having committed an illegal act